Estimating lifetime asbestos inhalation exposure of brake maintenance workers in Malaysia - Yusof, Muhammad Zubir; Zahaba, Maryam; Mohd Aris, M.S.; Abdul Hadi, H.; Maghpor, M.N.; Noraini, N.M.R. (2021)
Asbestos-containing products are still used in developing countries, including Malaysia. Malaysia has partially banned the use of asbestos (crocidolite) but not chrysotile. Exposure to chrysotile during brake maintenance can result in a range of diseases, including asbestosis, lung cancer, and mesothelioma. The aim of the study is to use retrospective exposure reconstruction techniques to estimate workers' lifetime asbestos exposure and assess their health risk.